Serosurvey of Schmallenberg Virus Infections in Sheep and Goat Flocks in Lower Saxony, Germany. Issue 4 (1st October 2013) - Helmer, C.; Eibach, R.; Tegtmeyer, P. C.; Humann–Ziehank, E.; Runge, M.; Ganter, M.
Summary Schmallenberg virus (SBV) infections can cause congenital musculoskeletal and vertebral malformations as well as neurological failures in foetuses of several ruminant species if susceptible mother animals were infected during early gestation. Blood samples gained from 17 goat and 64 sheep flocks in Lower Saxony (LS), Germany (January–May 2012), which is located in the core region of the 2011/2012 epidemic were tested for antibodies against SBV by ELISA to detect past exposure to SBV. A SBV‐specific questionnaire was raised in all flocks. The calculated median within‐herd prevalence was 43.8% (min–max: 5.6–93.3%) for goats and 58.7% (min–max: 6.5–100%) for sheep, showing that small ruminants in LS, especially goats, are still at risk of novel SBV infections in the following lambing seasons as not all animals have seroconverted yet. Statistical analysis revealed that goats have a significantly lower risk of SBV infections than sheep which might be explained by different host preferences of Culicoides ssp. as main vectors for SBV and different housing conditions.